Acute Distal Triceps Tendon Rupture Repair: Case Presentation and Surgical Technique. (August 2021) - Luthringer, Tyler A.; Lowe, Dylan T.; Egol, Kenneth A.
Abstract : This case presentation and surgical technique demonstrates a complete distal triceps tendon rupture repair with single-row suture anchor fixation through a posterior midline approach to the elbow in a 17-year-old male rugby player. Key procedure points include complete triceps mobilization for adequate excursion to facilitate repair, identification of the ulnar nerve, isolation and sharp debridement of torn tissue to healthy tendon, thorough debridement of the olecranon reattachment site, suture construct, and order of fixation to optimize tendon–bone apposition. Abstract : Summary: